Integrating fishers’ knowledge with oceanographic observations to understand changing ocean conditions in the Northeast United States - Olsen, Noelle A.; Bahr, Frank; Bethoney, N. David; Mercer, Anna M.; Gawarkiewicz, Glen (Frontiers in Marine Science, 2023)
Recent warming in the Northeast United States continental shelf ecosystem has raised several concerns about the impacts on the ecosystem and commercial fisheries. In 2014, researchers from the Commercial Fisheries Research Foundation and Woods Hole Oceanographic Institution founded the Shelf Research Fleet to involve fishers in monitoring the rapidly changing ocean environment and encourage sharing of ecological knowledge. The Shelf Research Fleet is a transdisciplinary, cooperative program that trains commercial fishers to collect oceanographic information by deploying conductivity, temperature, and depth (CTD) instruments while commercially fishing. A total of 806 CTD profiles have been collected by the Shelf Research Fleet through December 2022. Participating vessels can view the conductivity and temperature water column profiles they collect in real-time. These profiles help inform their fishing practices and give insights when unexpected species appear in their gear or if their catch composition changes from previous years. The data collected by the Shelf Research Fleet are shared with and processed by researchers from numerous partnering institutions. The Shelf Research Fleet data have been used by researchers to better understand oceanographic phenomena including marine heatwaves, shelf-break exchange processes, warm core rings, and salinity maximum intrusions onto the continental shelf. The scope of the Shelf Research Fleet has grown over time to include efforts to more directly link oceanographic results with biological observations to better understand how changing ocean conditions are affecting commercially important species. This article describes the approach, successes, challenges, and future directions of the Shelf Research Fleet and aims to outline a framework for a cost-effective research program that engages fishers in the collection of oceanographic data, strengthening partnerships between fishing industry members and the scientific community.